2016
DOI: 10.5144/0256-4947.2016.313
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Practice Guidelines on the Screening and Treatment of Precancerous Lesions for Cervical Cancer Prevention in Saudi Arabia

Abstract: BACKGROUNDCervical cancer is the third most common gynecological malignancy in Saudi women with an estimated incidence rate of 1.9 cases per 100 000 women-years. More than 40% of cervical cancer cases are diagnosed at advanced stages due to lack of a routine screening program in Saudi Arabia. Thus, national guidelines for routine screening and treatment of precancerous cervical lesions are needed.METHODSThe Saudi Centre for Evidence-Based Healthcare invited a panel of local experts and partnered them with a te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 39 publications
0
26
0
Order By: Relevance
“…Multiple studies have exhibited that CC is one of the most prevalent malignant tumor in women with a high mortality in developing countries and the drug resistance requires novel anti neoplasm drugs and neo‐chemotherapy strategies (Al‐Mandeel et al, ; Xia et al, ; Yang et al, ). More and more evidences show that aberrantly expressed miRNAs play vital role in the process of tumorigenesis of CC, and thorough understanding of the underlying mechanisms of the small, single‐stranded RNAs may contribute to new treatment regimens for patient with CC (Wang et al, ; Xu et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have exhibited that CC is one of the most prevalent malignant tumor in women with a high mortality in developing countries and the drug resistance requires novel anti neoplasm drugs and neo‐chemotherapy strategies (Al‐Mandeel et al, ; Xia et al, ; Yang et al, ). More and more evidences show that aberrantly expressed miRNAs play vital role in the process of tumorigenesis of CC, and thorough understanding of the underlying mechanisms of the small, single‐stranded RNAs may contribute to new treatment regimens for patient with CC (Wang et al, ; Xu et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Two were related to general gynecological cancer services in Arab countries (Ortashi & Al Kalbani, ) and general cancer control in the Gulf (Al‐Othman et al, ). Empirical research was not reported in two papers (Al‐Mandeel et al, , K. Sait, Bentley, Anfinan, & Power, ), leaving 13 for inclusion in the integrative review.…”
Section: Methodsmentioning
confidence: 99%
“…Of these 271 women, 143 (52.8%) will die due to the disease, including 27 (39.7%) at the child-bearing age [3]. A dramatic increase in the incidence of cervical cancer in Saudi Arabia is anticipated [4].…”
Section: Introductionmentioning
confidence: 99%